Adult and student perspectives on racial and ethnic equity‐informed school‐based strategies. Issue 10 (4th August 2021) - Lea, Charles H.; McCowan, Kristin J.; Jones, Tiffany M.; Malorni, Angela
Abstract: Although racial and ethnic equity‐informed school‐based strategies are important to addressing racialized structures and processes that create and sustain racial trauma, disadvantage and disparity, little is known about the process of embedding racial and ethnic equity in school‐based strategies and how adults and young people perceive them to promote a positive school climate and youth development. Using a qualitative research approach that included focus groups, this study examined student of color and school and community partner staff perceptions of the role and influence racial and ethnic equity‐informed school‐based strategies in one middle school have on the school's climate and students of color experiences and development. Findings suggest that racial and ethnic equity‐informed social and emotional learning strategies are important in facilitating positive student–teacher interactions and identity and social‐emotional development among students of color. Participant's experiences in and perceptions of the impact these strategies have on school climate and youth development substantiate the need to understand racial and ethnic equity as a process‐oriented approach that requires continuous improvement, rather than just an outcome‐focused endeavor. Implications for research and practice are discussed.